Sistem Online Pada Aplikasi Sistem Informasi Berbasis Desktop Menggunakan Virtual Private Network - Humaini, Irfan (Jurnal Ilmiah Teknologi dan Rekayasa, 2014)
Recently, data processing by online and real time has been a certainty. This is possible by information technology development, especially regarding to internet. Every companies or business that want to improve must follow the development in order to stay current and not miss the chance in the free-market competition as present. By understanding such condition, in the study, to improve the performance of a company which has not had desktop-based online and real time system information, the system information application is developed to be an online and real-time system information by keep use the existing and more advanced desktop-based system information application to connect every part and branch of the company which is expanded in some areas. It is done without extremely changing the exist system information such as being designed from the scratch and web-based. In development of the system information, the technology used is virtual private network (VPN), in this case, VPN LogMeIn Hamachi. The justification of using the VPN LogMeIn Hamachi technology or application is because it is considered to be safe, easy to install, quick and economic.Keywords: Virtual Private Network, LogMeIn Hamachi